Genres of rewriting in Second Temple Judaism: scribal composition and transmission - Zahn, Molly M. (University of Cambridge ESOL Examinations, 2020)
A study of the many different ways ancient Jewish scribes changed, or rewrote, the sacred and authoritative traditions they inherited.